Which Industries are shifting the Beveridge Curve? - Regis Barnichon; Michael Elsby; Bart Hobijn; Aysegul Sahin (Tinbergen Institute, 2011)
The negative relationship between the unemployment rate and the job openings rate, known as the Beveridge curve, has been relatively stable in the U.S. over the last decade. Since the summer of 2009, in spite of firms reporting more job openings, the U.S. unemployment rate has not declined in line with the Beveridge curve. We decompose the recent deviation from the Beveridge curve into different parts using data from the Job Openings and Labor Turnover Survey (JOLTS). We find that most of the current deviation from the Beveridge curve can be attributed to a shortfall in hires per vacancy. This shortfall is broad-based across all industries and is particularly pronounced in construction, transportation, trade, and utilities, and leisure and hospitality. Construction alone accounts for more than half of the Beveridge curve gap.
urn:NBN:nl:ui:31-1871/38553
Keywords: J23; J60; J63; 330; Beveridge Curve; job openings; measurement; search frictions; Beveridge-Kurve